'Money for nothing'. The role of robotic-assisted laparoscopy for the treatment of endometriosis. Issue 4 (October 2017) - Berlanda, Nicola; Frattaruolo, Maria Pina; Aimi, Giorgio; Farella, Marilena; Barbara, Giussy; Buggio, Laura; Vercellini, Paolo
Graphical Abstract: Highlights: Robotic treatment of endometriosis does not outweigh standard laparoscopy. Severe endometriosis, peritoneal disease and obesity are not indications for robotic surgery. Robotic surgery for endometriosis should be performed within controlled studies. Abstract: Despite higher costs for robotic-assisted laparoscopy (RAL) than standard laparoscopy (SL), RAL treatment of endometriosis is performed without established indications. PubMed/MEDLINE was searched for 'robotic surgery' and 'endometriosis' or 'gynaecological benign disease' from January 2000 to December 2016. Full-length studies in English reporting original data were considered. Among 178 articles retrieved, 17 were eligible: 11 non-comparative (RAL only) and six comparative (RAL versus SL). Non-comparative studies included 445 patients. Mean operating time, blood loss and hospital stay were 226 min, 168 ml and 4 days. Major complications and laparotomy conversions were 3.1% and 1.3%. Eight studies reported pain improvement at 15-month follow-up. Comparative studies were all retrospective; 749 women underwent RAL and 705 SL. Operating time was longer for RAL in five studies. Major complications and laparotomy conversions for RAL and SL were 1.5% versus 0.3% and 0.3% versus 0.5%. One study reported pain reduction for RAL at 6-month follow-up. RAL treatment of endometriosis did not provide benefits over SL, overall and among subgroups of women with severe endometriosis, peritoneal endometriosis and obesity. Available evidence is low-quality, and data regarding long-term pain relief and pregnancy rates are lacking. RAL treatment of endometriosis should be performed only within controlled studies.